2020
DOI: 10.3390/pharmaceutics12030286
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Reconstitutable Dry Suspension Containing Isoniazid for Flexible Pediatric Dosing

Abstract: Tuberculosis (TB) is a major cause of childhood death. Despite the startling statistics, it is neglected globally as evidenced by treatment and clinical care schemes, mostly extrapolated from studies in adults. The objective of this study was to formulate and evaluate a reconstitutable dry suspension (RDS) containing isoniazid, a first-line anti-tubercular agent used in the treatment and prevention of TB infection in both children and adults. The RDS formulation was prepared by direct dispersion emulsification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This usually involves the crushing or splitting or breaking of adult solid dosage forms into sizeable portions or even powders for administration with water, milk, juice, or even soft food to accommodate the pediatric patients. In some instances, physicians prescribe extemporaneously compounded antitubercular formulations for children, and the common challenge often associated with these kinds of orders is that their preparation and concentrations tend to vary from pharmacy to pharmacy and even one hospital to the other ([ 7 , 215 , 216 , 217 ]). These administration methods can potentially result in dosing inaccuracies, unwanted drug–food interactions, reduced drug potency, impaired formulation stability, disruption of formulation coating/external layering, compromised bioavailability, and inconvenience associated with caregiving, which ultimately leads to poor patient compliance, undesired pharmacotherapeutic outcomes and eventual onset of resistance [ 7 , 112 , 218 , 219 , 220 ].…”
Section: Pediatric Tuberculosis and Pharmaceutical Dosage Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…This usually involves the crushing or splitting or breaking of adult solid dosage forms into sizeable portions or even powders for administration with water, milk, juice, or even soft food to accommodate the pediatric patients. In some instances, physicians prescribe extemporaneously compounded antitubercular formulations for children, and the common challenge often associated with these kinds of orders is that their preparation and concentrations tend to vary from pharmacy to pharmacy and even one hospital to the other ([ 7 , 215 , 216 , 217 ]). These administration methods can potentially result in dosing inaccuracies, unwanted drug–food interactions, reduced drug potency, impaired formulation stability, disruption of formulation coating/external layering, compromised bioavailability, and inconvenience associated with caregiving, which ultimately leads to poor patient compliance, undesired pharmacotherapeutic outcomes and eventual onset of resistance [ 7 , 112 , 218 , 219 , 220 ].…”
Section: Pediatric Tuberculosis and Pharmaceutical Dosage Formsmentioning
confidence: 99%
“…It has also been reported that even older children, up till the age of eighteen, still struggle to swallow tablets that are more than 15 mm in diameter. These points further promote the “off-label” use of TB medicines and exacerbate the effects of inaccurate dosing that can eventually render the medicine ineffective, and potentially trigger drug resistance [ 7 , 227 , 231 , 232 ]. Liquid antitubercular preparations, on the other hand, are more child friendly and easier to swallow, but are often limited by their poor palatability and lack of dose uniformity, often resulting in the need to use more excipients such as sweeteners, stabilizers, etc.…”
Section: Pediatric Tuberculosis and Pharmaceutical Dosage Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may mean that the introduction of the test compounds may have inhibited cell growth but does not necessarily promote cell destruction or death-as it is with the case of cytotoxicity. Identified cellular responses resulting from cell exposure to test samples can be termed as dose-dependent and two-phased, an occurrence related with hormesis which, is a two-way adaptive reaction of cells (biological systems) to external stress such as xenobiotics, environmental changes (e.g., pH, temperature) [60]. For both implemented assays, the optimized PZA orodispersible formulation demonstrated no significant reduction in cell viability.…”
Section: Cytobiocompatibility Evaluationmentioning
confidence: 99%
“…Finally, this SI has included the paper by Adeleke et al [12] that has formulated and evaluated a reconstitutable dry suspension (RDS) containing isoniazid, a first-line antitubercular agent used in the treatment and prevention of TB infection in both children and adults. These formulations have been prepared by direct dispersion emulsification of an aqueous-lipid particulate interphase coupled with lyophilization and dry milling.…”
mentioning
confidence: 99%